Exploring the relationship between social media dependence and internet addiction among college students from a bibliometric perspective - Dong, Ruotong; Yuan, Dongfeng; Wei, Xue; Cai, Jingyi; Ai, Zhongzhu; Zhou, Shiquan (Frontiers in Psychology, 2025)
BackgroundSocial media use among college students often leads to psychological dependence, resulting in a rising number of internet addictions. The link between social media dependence and addiction is garnering increasing attention.ObjectiveThe aim of this study was to analyze and discuss the research trends and hotspots on social media dependence and internet disorder among college students by bibliometric methods.MethodsRelevant studies on social media dependence and online addiction among college students were retrieved from the Web of Science (WoS) database spanning the years 2013 to 2024. We delineated the distribution of publications to identify the core productivity within the field. VOSviewer software was employed to conduct network visualization analyses of countries, authors, journals, and keywords, aiding in a comprehensive understanding of the research trends and hotspots in this domain.ResultsFrom the WoS database, we retrieved 302 publications, and 167 publications were included after screening. The findings revealed: (1) a steady increase in publications and citations, particularly accelerating after 2019. (2) The most productive journal is Computers in human behavior, the most productive research area is Psychology, and the most productive author, institution, and country are Professor Griffiths MD, Nottingham Trent University and China, respectively. (3) Collaborative network analysis indicated that there were multiple research groups in this field, yet the connections among countries and authors remain relatively limited. (4) Co-citation analysis of journals revealed that this field was interdisciplinary, primarily integrating psychology, psychiatry, and behavioral science. (5) Keyword analysis identified two major research hotspots: the relationship between college students’ social media dependence and internet addiction, and the mediating factors influencing college students’ social media dependence and internet addiction. The mechanism of internet addiction is an emerging research frontier.ConclusionThis analysis outlines the progress and directions of research on college students’ social media dependence and internet addiction. It offers a comprehensive examination of the latest frontiers and trends, providing theoretical support for regulating the use of electronic products and implementing mental health interventions in college students.